2000
DOI: 10.1086/301283
|View full text |Cite
|
Sign up to set email alerts
|

The Parsec-Scale Structure and Evolution of the Nearby Fanaroff-Riley Type II Radio Galaxy Pictor A

Abstract: We present very long baseline interferometry (VLBI) images of the core emission from a nearby bright FR II radio galaxy, Pictor A, revealing its parsec-scale jet structure and evolution for the Ðrst time. These data constitute a signiÐcant addition to our knowledge of powerful radio galaxies on the smallest scales, e †ectively doubling the number studied at this resolution. The jet, 14 h~1 pc in projected extent, is directed west of the core for the Ðrst 5 h~1 pc and then appears to bend approximately 40¡ to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 28 publications
6
29
2
Order By: Relevance
“…The corresponding upper limits to the jet viewing angles are thus θ j 20 • . Interestingly, mildly relativistic velocities are inferred for 3C 390.3 and Pictor A (β app up to 2.2 and 1.6, respectively; Kellermann et al 2004;Tingay et al 2000), both of which are good candidates for future Fermi-LAT detections (see Table 2 and Figure 8). These four BLRGs, not coincidentally, have the brightest radio/VLBI cores in the analyzed sample, consistent also with a relatively large degree of relativistic beaming (see the comment in the Appendix).…”
Section: Discussionmentioning
confidence: 94%
“…The corresponding upper limits to the jet viewing angles are thus θ j 20 • . Interestingly, mildly relativistic velocities are inferred for 3C 390.3 and Pictor A (β app up to 2.2 and 1.6, respectively; Kellermann et al 2004;Tingay et al 2000), both of which are good candidates for future Fermi-LAT detections (see Table 2 and Figure 8). These four BLRGs, not coincidentally, have the brightest radio/VLBI cores in the analyzed sample, consistent also with a relatively large degree of relativistic beaming (see the comment in the Appendix).…”
Section: Discussionmentioning
confidence: 94%
“…X-ray emission from the nucleus, the jet to the west of the nucleus, the western radio hot spot, and the eastern radio lobe was detected with Chandra (Wilson et al, 2001). Tingay et al (2000) found subluminal motions in the western jet. No parsec-scale counterjet has been detected so far.…”
Section: −458mentioning
confidence: 97%
“…Interpreting the variable component as unboosted (D ∼ 1) emission from a central blazar, and assuming standard jet parameters, the emission region would have an inclination angle to the line of sight of θ ≈ 25 • , and the observed factor-of-two increase in flux density within three years could be explained by a change of inclination angle by ≈3 • towards the observer. However, this would require a rotational speed significantly larger than that inferred from VLBI observations of the central jet of Pic A, if these are interpreted in a precessing jet model (Tingay et al 2000). An interpretation of the flare in Pic A as due to a shock in the jet would be more consistent with the misaligned-blazar picture: with a Doppler factor D ∼ 10 the Pic A flare would be comparable in intrinsic time scale and peak frequency with the exceptional outburst in 3C 454.3 observed in 2005.…”
Section: Variability In Unbeamed Sourcesmentioning
confidence: 99%